Effect of Chitosan Coating Containing Active Agents on Microbial Growth, Rancidity and Moisture Loss of Meatball During Storage - Yudi Pranoto; Sudip Kumar Rakshit (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2008)
Edible coatings based on chitosan were applied on meatball product in order to preserve quality during storages atambient and refrigeration temperatures. To improve its efficacy, chitosan coatings were incorporated with garlic oil0.2%, potassium sorbate 0.1 % and nisin 51,000 IU. The qualities of meatball assessed were total microbial growth, TBA value and percentage of moisture loss. All chitosan coatings suppressed microbial growth in meatball and strong- ly revealed when stored at refrigeration temperature. Incorporating garlic oil 0.2% into chitosan coating resulted in a greater reduction of rancidity level in meatball for both storages. Moisture loss of meatball was significantly reduced by all chitosan coatings and obviously shown when stored at refrigeration temperature.